Music And Language: A Stress Analysis of English Song Lyrics - Suharto, S. (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2004)
Music especially a song has a stress pattern of musical rhythm. In the first bar, there is a strong beat called accent. Like a music, English is often described as stress-time language. There some rules of the language in pronunciation.Ã‚Â The purpose of this study is to know the tendency English stress pattern applied in English song lyrics viewed from the stress pattern of music rhythm. This study is a quantitative one by using musical approach. Sample of this study uses two song analysis is used. And to discuss the finding analysis the musical approach especially music composition is applied. The results of this study are (1) most of the syllables of English stress pattern are matched to the stress pattern of the musical rhythm in which have different meter signature, 78.15 % in Song 1 and 97.31 % in Song 2. (2) most word classes whose s syllables of word stresses are matched to the stress pattern of musical rhythm are nouns, 52,27 % in Song 1 and 67.27 % in Song 2. Based on the result suggestions in this study are that it is important for composers to consider to the two important elements of the English song, lyric and beats or meter signature, to get good song, and other study related to this study are needed in order that this finding can be generalized to all of English song Lyrics